Squaring circles and hybridizing school design: a principal’s autoethnography of socialization and personal wellness - Stevens, Curtis L. (Kansas State University, 2019)
This autoethnography explores a personalized account of an assistant principal making the transition to the head principal position during the design phase of a new high school, focusing on salient critical incidents. The purpose of this study is to describe and interrogate contextually rich experiences that integrate educational leadership, and personal wellness as depicted through work life balance. Findings of this study might offer possibilities for other practitioners to avoid the mistakes I made, and benefit from the practices that proved successful. This study uses qualitative research as its foundation and as a means to study a social context, while causing as little disruption as possible in the natural setting (Eaton, 2002; Merriam, 1998). Under the umbrella of qualitative research, from a constructivist lens, in the form of an autoethnography, a qualitative genre of research, I play the role of both the researcher and the participant. As a researcher, I use ethnographic methods to explore and interrogate my experiences as a participant within the context of Educational Leadership culture specifically in the MidWest, and broadly in the U.S. I uncover a pattern of dynamic dichotomies, common for practicing school leaders, who frequently find themselves striving to find balance between work and family, as well as navigating the external and internal political factions that exist in every school culture. Such findings indicate an essential need for more qualitative scholarship to uncover the principal’s personal wellness both inside and out. The implications for this study raise a need for dialogue across Educational Leadership practitioners and trainers to explore how others make such negotiations and balance personal wellness. Further dialogue with Educational Leadership training program could examine the curriculum and training to interrogate whether such trainings are culturally homogenous and in need of diversification, whether there should be focus on exploring work life balance skills as part of the training. Due to the dearth of such personally situated insights, yet with the critical need for such insights, it is clear that there needs to be more discourses and space making for practitioners’ experiences juxtaposed against the broader culture of educational leadership to explore issues of transition, socialization, leadership training, and personal wellness in a field with high pressure, rampant turnover, and feelings of isolation.
Keywords: School design; Autoethnography; Principal; Socialization; Leadership; Administration